AN OVERVIEW ON INTERNATIONALISATION WITHIN THE UNITED KINGDOM HIGHER EDUCATION - Emad Al-Mahdawi (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
This study aimed to analyse how the trend towards internationalisation for higher education has been constituted considering the perspectives of solidarity. Internationalisation is understood as integration among worldwide higher education institutions. The work discusses the process of the UK universities internationalisation and analyses how this process has occurred, where the internationalisation was the result of a formal policy of the institution or if, in reality, internationalisation was the result of actions predominantly determined by individuals. It focuses on the impacts of globalisation on universities caused by Brexit. It also emphasises the concepts such as internationalisation and mobility, globalisation and higher education research collaboration, and EU funding. The research results reduce the literature on the internationalisation of higher education, particularly the dynamics of the internationalisation of universities located in developing countries. The research also reveals and emphasises the internationalisation actions, that is, the importance of teachers, researchers and administrators as catalysts of this process. Universities of the UK should find new strategies for attracting more international students, effective digital media marketing, highly branding marketing campaigns, and worldwide satellite campuses can make significant changes.